Analysis of Atmospheric Vertical Structure During Hail in Tangerang: A Comparative Study of ECMWF Model Data and Radiosonde Observations - Dhanu Prakoso; Aries Kristianto (Jurnal Sains dan Terapan Kimia, 2026)
Hail is an extreme weather event in tropical regions with local characteristics, short duration, and difficult to predict precisely. The hail event in Tangerang on October 31, 2025, is an important anomaly to study in order to understand the atmospheric structure that triggers massive instability in urban areas. This study aims to identify the vertical conditions of the atmosphere through a comparative study between global numerical model data from the European Centre for Medium-Range Weather Forecasts (ECMWF) and in-situ Radiosonde observation data. The methodology used is a case study approach by integrating remote sensing data from the Himawari-9 Satellite and C-Band Weather Radar to validate the structure of storm cells. Thermodynamic parameters such as Convective Available Potential Energy (CAPE) and freezing level profiles are extracted using Python programming to evaluate the model's ability to represent atmospheric lability conditions. The results of this study are expected to provide a reference for weather forecasters regarding the effectiveness of using global model data as an alternative to limited observational data in the early detection of extreme convective phenomena in Indonesia.